2008
DOI: 10.2172/928278
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of Soil Desiccation for Vadose Zone Remediation: Report for Fiscal Year 2007

Abstract: SummaryApart from source excavation, the options available for the remediation of vadose zone metal and radionuclide contaminants beyond the practical excavation depth (0 to 15 m) are quite limited. Of the available technologies, very few are applicable to the deep vadose zone with the top-ranked candidate being soil desiccation. An expert panel review of the work on infiltration control and supplemental technologies identified a number of knowledge gaps that would need to be overcome before soil desiccation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Thus, the impact of non‐uniform temperature is to spatially spread out the evaporation process. In laboratory flow cell tests, very sharp transitions between the zone of desiccation and nondesiccated zones were observed when temperature was relatively constant due to fast heat transfer from the flow cell walls that minimized evaporative cooling impact on temperature (Ward et al, 2008; Oostrom et al, 2009). For field applications, evaporative cooling can decrease temperatures over a large extent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the impact of non‐uniform temperature is to spatially spread out the evaporation process. In laboratory flow cell tests, very sharp transitions between the zone of desiccation and nondesiccated zones were observed when temperature was relatively constant due to fast heat transfer from the flow cell walls that minimized evaporative cooling impact on temperature (Ward et al, 2008; Oostrom et al, 2009). For field applications, evaporative cooling can decrease temperatures over a large extent.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory and modeling studies (Ward et al, 2008; Oostrom et al, 2009, 2012a,2012b; Truex et al, 2011) suggest that the overall performance of desiccation in limiting water and contaminant flux to the groundwater is a function of the final moisture content, contaminant concentration, sediment properties, size of the desiccated zone, the hydraulic properties and conditions in surrounding subsurface zones, and the net surface recharge rate. For instance, Truex et al (2011) demonstrated through numerical modeling that combinations of a surface infiltration barrier and subsurface desiccation reduced the contaminant flux and maximum resulting groundwater contaminant concentration compared to no‐treatment or surface‐barrier‐only scenarios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All these applications are passive in nature. In combination with surface flux control, active subsurface desiccation through injection of relatively dry air has recently been proposed as a means to reduce water contents in subsurface layers (Fluor Hanford, Inc., 2006; Ward et al, 2008; Truex et al, 2011). The evaporation process resulting from dry air injection removes pore water and results in lower moisture content and aqueous‐phase relative permeability in the desiccated zone (Oostrom et al, 2009; Truex et al, 2011, 2012).…”
mentioning
confidence: 99%
“…Recent field‐scale modeling studies (Ward et al, 2008; Truex et al, 2011) have indicated that the overall performance of desiccation in limiting water and contaminant flux to the groundwater is a function of the final moisture content (after desiccation), contaminant concentration, extent of the desiccated zone, the hydraulic properties and conditions in surrounding subsurface zones, and the net surface recharge rate. These modeling studies demonstrated that the desiccation rate is increased with higher temperature and lower relative humidity of the injected dry gas.…”
mentioning
confidence: 99%